2017
DOI: 10.1038/cddis.2017.127
|View full text |Cite
|
Sign up to set email alerts
|

p45 NF-E2 regulates syncytiotrophoblast differentiation by post-translational GCM1 modifications in human intrauterine growth restriction

Abstract: Placental insufficiency jeopardizes prenatal development, potentially leading to intrauterine growth restriction (IUGR) and stillbirth. Surviving fetuses are at an increased risk for chronic diseases later in life. IUGR is closely linked with altered trophoblast and placental differentiation. However, due to a paucity of mechanistic insights, suitable biomarkers and specific therapies for IUGR are lacking. The transcription factor p45 NF-E2 (nuclear factor erythroid derived 2) has been recently found to regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Next, we tested whether CREB-binding proteins are required for CGB expression. Administration of C646, a selective inhibitor of CBP and p300 [16], significantly impaired forskolin-induced CGB expression in BeWo cells by 57.1% after 24 h (Fig. 5e).…”
Section: Creb-binding Proteins Are Required For Efficient βHcg Synthesismentioning
confidence: 94%
“…Next, we tested whether CREB-binding proteins are required for CGB expression. Administration of C646, a selective inhibitor of CBP and p300 [16], significantly impaired forskolin-induced CGB expression in BeWo cells by 57.1% after 24 h (Fig. 5e).…”
Section: Creb-binding Proteins Are Required For Efficient βHcg Synthesismentioning
confidence: 94%
“…The PPAR signaling pathway also plays a role, as Pparg null trophoblast cells fail to undrego terminal syncytium formation, which disrupts the integrity of the vascular exchange interface and restricts growth of the fetus ( 78 , 79 ). Members of the PPAR family, as well as GCM1 and its antagonist NFE2 have been implicated in human IUGR placentas ( 80 82 ), demonstrating that abnormal differentiation of the villous trophoblast, especially of the syncytiotrophoblast layer, also contributes to placental insufficiency and IUGR in humans.…”
Section: Placental Structures Linked To Embryonic Growthmentioning
confidence: 99%
“…Although fetal growth in Gcm1 +/− conceptuses is not affected, wild-type females carrying Gcm1 +/− conceptuses develop late gestational hypertension similar to what is seen in pre-eclampsia patients. Human placentas from IUGR pregnancies express reduced levels of NFE2 , leading to upregulation of GCM1 and excessive development of the syncytium ( 82 ), suggesting that similar molecular pathways operate in the establishment of the human placental IHM and may contribute to IUGR when disrupted.…”
Section: Placental Structures Linked To Embryonic Growthmentioning
confidence: 99%
“… 9 , 10 Moreover, IUGR is associated with an increased risk of fetal-originated metabolic syndrome and cardiovascular disease. 10 , 11 , 12 Previous studies 7 , 13 , 14 have reported that placental insufficiency, intrauterine infection, fetal chromosome anomalies, gestational hypertension, and preeclampsia are risk factors for IUGR. However, the etiopathology of IUGR has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%